2021
DOI: 10.1155/2021/6661620
|View full text |Cite
|
Sign up to set email alerts
|

[D-Ala2, D-Leu5] Enkephalin Inhibits TLR4/NF-κB Signaling Pathway and Protects Rat Brains against Focal Ischemia-Reperfusion Injury

Abstract: Background. Cerebral ischemia-reperfusion (I/R) injury is the main cause of acute brain injury, which is a life-threatening disease due to the lack of effective treatments. [D-Ala2, D-Leu5] enkephalin (DADLE) is a synthetic delta-opioid receptor agonist that is reported to confer neuroprotective effect; however, the underlying mechanism is still being explored. The purpose of the present study is to determine whether DADLE administrated intracerebroventricularly could attenuate the cerebral I/R injury, to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…An early study demonstrated that activating DOR using DOR agonist SNC-121 attenuated TNF-α induced matrix metalloproteinase-2 (MMP-2) secretion in the glia cells, and the effects of DOR were realized by negatively regulating the p38 MAPK and NF-κB signaling [ 125 ]. More recently, a group of researchers established a MCAO rat model, in which cerebral ischemia-reperfusion injury increased TLR4 and NF-κB expression in the rat’s brain, which was remarkably inhibited by DOR-specific agonist DADLE [ 126 ]. NF-κB was regarded as one of the crucial signaling targets in DOR-mediated long-term neuroprotection.…”
Section: Major Pathways For Dor Modulation Of Microglial Neuroinflamm...mentioning
confidence: 99%
“…An early study demonstrated that activating DOR using DOR agonist SNC-121 attenuated TNF-α induced matrix metalloproteinase-2 (MMP-2) secretion in the glia cells, and the effects of DOR were realized by negatively regulating the p38 MAPK and NF-κB signaling [ 125 ]. More recently, a group of researchers established a MCAO rat model, in which cerebral ischemia-reperfusion injury increased TLR4 and NF-κB expression in the rat’s brain, which was remarkably inhibited by DOR-specific agonist DADLE [ 126 ]. NF-κB was regarded as one of the crucial signaling targets in DOR-mediated long-term neuroprotection.…”
Section: Major Pathways For Dor Modulation Of Microglial Neuroinflamm...mentioning
confidence: 99%
“…The model of transient focal MCAO rat was established in this experiment, which was based on a previous study [7]. 10% chloral hydrate 300 mg/kg was injected intraperitoneally for anaesthesia, and no response of the rat tail was taken as an indication of successful anaesthesia.…”
Section: Mcao Animal Model Construction and Treatmentmentioning
confidence: 99%
“…At present, D-peptide is frequently used, and it is recognized as a potent and promising drug. Enkephalin (D-Ala2, D-Leu5) is effective to attenuate cerebral I/R injury [154]. D-Trp-6-LH-RH is used for the treatment of advanced prostatic cancer/advanced ovarian cancer, etc.…”
Section: Incorporating D-aas Into Drugs Afford Stronger Biostability ...mentioning
confidence: 99%